2023
DOI: 10.1111/tops.12646
|View full text |Cite
|
Sign up to set email alerts
|

How to Become a Memory: The Individual and Collective Aspects of Mnemicity

Abstract: Human adults distinguish their mental event simulations along various dimensions—most prominently according to their “mnemicity”: we track whether these simulations are outcomes of past personal experiences or not (i.e., whether we are “remembering” or “imagining”). This distinction between memory and imagination is commonly thought to reflect a deep architectural distinction in the mind. Against this idea, I argue that mnemicity is not based on a fundamentalstructural difference between memories and imaginati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Like false memories more generally, memory distrust has been suggested to be related to people’s susceptibility to social influence (Zhang, Otgaar, et al, 2022), which has been found to be shaped by self-construal, with people who are more interdependent and exhibiting greater compliance to others (Oeberst & Wu, 2015). Furthermore, it has been argued that judgments of mnemicity—that is, the attributions of mental representations as being memories—are a result of metacognitive and social construction processes that are influenced by collective norms (Mahr, 2023; Mahr et al, 2023). That is to say, the “criteria” for what counts as memory may differ across cultures.…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Like false memories more generally, memory distrust has been suggested to be related to people’s susceptibility to social influence (Zhang, Otgaar, et al, 2022), which has been found to be shaped by self-construal, with people who are more interdependent and exhibiting greater compliance to others (Oeberst & Wu, 2015). Furthermore, it has been argued that judgments of mnemicity—that is, the attributions of mental representations as being memories—are a result of metacognitive and social construction processes that are influenced by collective norms (Mahr, 2023; Mahr et al, 2023). That is to say, the “criteria” for what counts as memory may differ across cultures.…”
Section: Cultural Differencesmentioning
confidence: 99%